Equity in Health: Consideration of Race and Ethnicity in Precision Medicine. Issue 11 (November 2020) - Edwards, Todd L.; Breeyear, Joseph; Piekos, Jacqueline A.; Velez Edwards, Digna R.
Abstract : The causes for disparities in implementation of precision medicine are complex, due in part to differences in clinical care and a lack of engagement and recruitment of under-represented populations in studies. New tools and large genetic cohorts can change these circumstances and build access to personalized medicine for disadvantaged populations.